2022
DOI: 10.4093/dmj.2021.0319
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Ketone Levels and Cardiometabolic Efficacy of Dapagliflozin versus Sitagliptin among Insulin-Treated Chinese Patients with Type 2 Diabetes Mellitus

Abstract: Background: Insulin-treated patients with long duration of type 2 diabetes mellitus (T2DM) are at increased risk of ketoacidosis related to sodium-glucose co-transporter 2 inhibitor (SGLT2i). The extent of circulating ketone elevation in these patients remains unknown. We conducted this study to compare the serum ketone response between dapagliflozin, an SGLT2i, and sitagliptin, a dipeptidyl peptidase-4 inhibitor, among insulin-treated T2DM patients.Methods: This was a randomized, open-label, active comparator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
(55 reference statements)
0
4
1
Order By: Relevance
“…The normal value is E/A > 1, and E/A < 1 is the manifestation of reduced ventricular diastolic function. In the present study, no statistically significant difference between the two groups was observed in the included studies ( 10 13 ). In contrast, some researchers believe that SGLT-2i could increase E/A after taking SGLT-2i.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…The normal value is E/A > 1, and E/A < 1 is the manifestation of reduced ventricular diastolic function. In the present study, no statistically significant difference between the two groups was observed in the included studies ( 10 13 ). In contrast, some researchers believe that SGLT-2i could increase E/A after taking SGLT-2i.…”
Section: Discussioncontrasting
confidence: 65%
“…A total of four articles ( 10 13 ) were included in the E/A study. There was no significant difference in E/A between the experimental and control groups (SMD −0.01, 95% CI −0.22 to 0.20, I 2 = 0%, p = 0.908) ( Figure 5D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants were T2D patients on background insulin therapy, and were randomized in a 1:1 ratio to an open‐label SGLT2i or DPP4i treatment to compare the serum ketone response and other metabolic changes. In this post‐hoc analysis, all DISTINCTION participants were included and their inclusion/exclusion criteria were described in detail previously 11 . The primary endpoint of the current study was the change in LS measured by vibration‐controlled transient elastography (VCTE).…”
Section: Methodsmentioning
confidence: 99%
“…XL probe was used only when M probe failed to produce valid and reliable measurements. LS and controlled attenuation parameter (CAP), which reflected hepatic fibrosis and steatosis, respectively, were measured by experienced operators with satisfactory interobserver reliability 11 . Both measurements were represented by the median of 10 reliable measurements.…”
Section: Methodsmentioning
confidence: 99%